2011
DOI: 10.1111/j.1439-0418.2011.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and implications of Andean potato weevil infestation sources for its management in the Andean region

Abstract: The Andean potato weevil Premnotrypes suturicallus Kuschel (Coleoptera: Curculionidae) is one of the most damaging potato (Solanum spp.) pests in the Andes. The objective of this study was to get a better understanding of weevil infestation sources and its distribution in potato fields as well as on the effect of potato cropping intensity and farmers’ harvest practices on weevil infestation to provide better clues for its management. For this purpose, a methodology was developed to assess weevil field densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…aFarmers apply a layer of ash directly below the potato seed at the time of planting; this practice is intended to kill potato weevils.bFertilization can influence crop defenses against herbivores [17].cMany agronomists recommend hilling the plants (piling dirt up around the stem of the plant) higher to lengthen the distance weevil larvae must travel to find tubers.dEarly harvest shortens the exposure of tubers to neonate larvae [18].eLarger fields have lower perimeter to area ratios and have been suggested to have lower infestations [19].fEarly emerging plants may experience greater infestations [20].gPlanting density may influence the abundance of many insect pests [21].hPlanting potatoes following a potato planting should lead to very high infestations [19], but implementing a single host free period should eliminate this risk. Rotation 2007 indicates if potatoes were sown in the field the previous season while Rotation 2006 indicates if potatoes were sown there two seasons before the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…aFarmers apply a layer of ash directly below the potato seed at the time of planting; this practice is intended to kill potato weevils.bFertilization can influence crop defenses against herbivores [17].cMany agronomists recommend hilling the plants (piling dirt up around the stem of the plant) higher to lengthen the distance weevil larvae must travel to find tubers.dEarly harvest shortens the exposure of tubers to neonate larvae [18].eLarger fields have lower perimeter to area ratios and have been suggested to have lower infestations [19].fEarly emerging plants may experience greater infestations [20].gPlanting density may influence the abundance of many insect pests [21].hPlanting potatoes following a potato planting should lead to very high infestations [19], but implementing a single host free period should eliminate this risk. Rotation 2007 indicates if potatoes were sown in the field the previous season while Rotation 2006 indicates if potatoes were sown there two seasons before the study.…”
Section: Methodsmentioning
confidence: 99%
“… d Early harvest shortens the exposure of tubers to neonate larvae [18] . e Larger fields have lower perimeter to area ratios and have been suggested to have lower infestations [19] . f Early emerging plants may experience greater infestations [20] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…oca, maize, mashua) or which are part of the same crop rotation (e.g. barley, broad beans, maize, mashua, oats, oca, quinoa) (Fries and Tapia, 2007 ; Ríos and Kroschel, 2011 ). Indeed, López and Herman ( 2004 ) reported that no oviposition could be found on stems of barley, oats, and stover, contrary to closely related potato and oca weevils ( Premnotrypes spp.…”
Section: Pest Categorisationmentioning
confidence: 99%